Hubungan Antara Kelengkapan Sumber Belajar Dan Motivasi Belajar Siswa Dengan Hasil Belajar Geografi - Erni Mentari; Sumadi Sumadi; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2019)
This study aims to find out about the relationship between the completeness of learning resources and learning motivation with the results of geography learning of the first grade students The research method used is correlational. The data collecting technique used in this research is documentation and questionnaires. The data analysis used is product moment correlation. Based on the results of data analysis, it shows that: (1) there is a positive and significant correlation between the completeness of learning resources owned by students at home with the students' learning outcomes on the subjects of geography of the first grade students in SMA Negeri 1 Tumijajar, the correlation coefficient obtained is rxy = 0,736. rtabel = 0,235. . (2) There is a high positive correlation between students' learning motivation and students' learning outcomes in geography subjects of the first grade students in SMA Negeri 1 Tumijajar, with rxy = 0,606. rtabel = 0,235.Penelitian ini bertujuan untuk mengetahui hubungan antara kelengkapan sumber belajar dan motivasi belajar dengan hasil belajar geografi siswa. Metode penelitian yang digunakan adalah metode penelitian korelasional. Pengumpulan datanya menggunakan tehnik dokumentasi dan angket. Analisis datanya menggunakan korelasi product moment. Berdasarkan hasil analisis data menunjukkan bahwa: (1) ada hubungan positif dan signifikan antara kelengkapan sumber belajar yang dimiliki siswa dirumah dengan hasil belajar siswa pada mata pelajaran Geografi Siswa Kelas X SMA Negeri 1 Tumijajar, diperoleh koefisien korelasi rxy = 0,736. rtabel = 0,235. (2) Terdapat hubungan positif yang cukup tinggi antara motivasi belajar siswa dengan hasil belajar siswa pada mata pelajaran geografi siswa kelas X SMA Negeri 1 Tumijajar, diperoleh rxy = 0,606. rtabel = 0,235.Kata kunci: hasil belajar, kelengkapan sumber belajar, motivasi siswa